From Authenticity to Sacrifice: Investigating the Link through Identity Fusion - Kurniawan, Aryodi Wahyu; Muluk, Hamdi; Milla, Mirra (UI Scholars Hub, 2026)
Urban environments, with their dense networks, mobility, and exposure to diverse ideologies, create conditions that can strengthen group attachment but also heighten vulnerability to religious extremist recruitment. Understanding the psychological processes behind such commitment is therefore essential. Identity fusion, a deep sense of oneness with a group and its members, is a key mechanism underlying willingness to sacrifice for the group. This study investigates how fusion develops through fulfillment of the psychological need for authenticity, defined as the need to be one’s true self within the group. Two studies were conducted among Muslim participants in Indonesia. Study 1 (N = 315) found that authenticity satisfaction predicted both identity fusion and willingness to sacrifice, with fusion mediating this relationship. Study 2 (N = 199) showed that perceived self-verification, or being seen by others as one sees oneself, predicted fusion through authenticity, which in turn influenced willingness to sacrifice. These findings suggest that fusion may arise from the fulfillment of relational needs, particularly authenticity. Recognizing authenticity as a pathway to fusion highlights a psychological vulnerability exploited by extremist groups and suggests practical avenues for prevention, such as strengthening inclusive communities, promoting trust-building, and fostering spaces for authentic self-expression.